2014
DOI: 10.1002/anie.201311103
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Catalytic Aerobic Functionalization of Phenols

Abstract: The importance of aromatic C-O, C-N, and C-S bonds necessitates increasingly efficient strategies for their formation. Herein, we report a biomimetic approach that converts phenolic C-H bonds into C-O, C-N, and C-S bonds at the sole expense of reducing dioxygen (O2) to water (H2O). Our method hinges on a regio- and chemoselective copper-catalyzed aerobic oxygenation to provide ortho-quinones. ortho-Quinones are versatile intermediates, whose direct catalytic aerobic synthesis from phenols enables a mild and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 65 publications
(2 reference statements)
1
86
0
2
Order By: Relevance
“…This observation suggests the initial formation of 4-tertbutylquinone [58] and further reaction to the coupled ortho-quinone 4-(tert-butyl)-5-(3-(tert-butyl)phenoxy) cyclohexa-3,5-diene-1,2-dione [21,22] with a TON of 20 for CuL imz 1 and a TON of 6 for CuBIMZ (ε = 898 L mol −1 cm −1 at λ = 425 nm). The corresponding NMR spectra (Figs.…”
Section: Tyrosinase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests the initial formation of 4-tertbutylquinone [58] and further reaction to the coupled ortho-quinone 4-(tert-butyl)-5-(3-(tert-butyl)phenoxy) cyclohexa-3,5-diene-1,2-dione [21,22] with a TON of 20 for CuL imz 1 and a TON of 6 for CuBIMZ (ε = 898 L mol −1 cm −1 at λ = 425 nm). The corresponding NMR spectra (Figs.…”
Section: Tyrosinase Activitymentioning
confidence: 99%
“…In 2013, Herres-Pawlis et al presented catalytic copper(I) model systems supported by bis(pyrazolyl)methane ligands which exhibit room temperature stable peroxo intermediates [20]. More recently, Lumb et al demonstrated catalytic conversions of different monophenols to a variety of organic products [21][22][23][24][25][26]. During the last years our group published a number of new copper(I) complexes functioning as model systems for tyrosinase [2,19,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Our strategy relies on a catalytic aerobic alternative to Maumy's stoichiometric oxygenative coupling, which we reported recently. 21 Based on Maumy's precedent, we expected that a substitution of 1a with alcohols under basic conditions would provide 4-alkoxy-ortho-quinones, where diversity at R 1 would be derived from readily available phenol starting materials. Under acidic conditions, we suspected that substitution would provide the thermodynamically favored paraisomer, affording either configuration of the quinone in a two-step process from the phenol.…”
Section: Introductionmentioning
confidence: 99%
“…9 Typical conditions involve stirring a solution of phenol for 4 hours under 2 atm O 2 in the presence of 4 mol% of [Cu I (CH 3 CN) 4 ](PF 6 ) and 5 mol% of N,N′-di-tert-butylethylenediamine (DBED). 9 Typical conditions involve stirring a solution of phenol for 4 hours under 2 atm O 2 in the presence of 4 mol% of [Cu I (CH 3 CN) 4 ](PF 6 ) and 5 mol% of N,N′-di-tert-butylethylenediamine (DBED).…”
mentioning
confidence: 99%
“…Among the Cu I species that were probed ( Table 1, entries 1-9), those with weakly coordinating anions such as PF 6 − or sulfonates displayed varying levels of catalytic activity whereas insoluble species (entries [4][5][6][7][8][9] were generally poor at initiating the reaction. Exceptions are Cu I Cl, Cu I CN and Cu I 2 O, but these precatalysts lead to low selectivity.…”
mentioning
confidence: 99%